NILAI-NILAI PENDIDIKAN KARAKTER PADA BUKU AJAR BAHASA JAWA TINGKAT SD KURIKULUM DIY - Biya Ebi Praheto; Octavian Muning Sayekti; Anang Sudigdo (LP2M Universitas Sarjanawiyata Tamansiswa, 2016)
This study to analyze and describe the educational values of characters contained in java textbooks of elementary school of curriculum DIY. This research expected to produce the findings on any character education in accodance with the guide lines of character education and culture of the ministry of National Education and Culture. The method used in this research is descriptive qualitative approach in order to describe the educational values of characters cntained in Java textbooks of Elementary School of Curriculum DIY the published by Erlangga, Tiga Serangkai, and Yudistira. Based on research that has been done is produced findings that not all the values of character education according to the guidelines of character education and culture of the Ministry of National Education and Culture totaling eighteen value of character education, contained in the Java language textbook published by Yudistira, Erlangga, and the Tiga Serangkai. Therefore, researchers gave suggestions to the author of textbooks, in order to pay more attention to the contents of the content of a book he wrote. Especially in terms of integrating the values of education. then for teachers, to be more selective in choosing books that will be used to teach. On the other hand, teachers should know and understand the values of character education contained in the book uses.Keywords: character, textbooks, javanesse language